Implications of Immune Checkpoint Expression During Aging in HIV-Infected People on Antiretroviral Therapy - de Armas, Lesley R. (AIDS Res Hum Retroviruses, 2019)
Immune checkpoint molecules (ICMs) regulate T cell responses. In chronic viral infections and cancer, where antigens can persistently stimulate the immune system, ICMs can serve as a barrier to effective immune responses. The role of ICMs in the setting of systemic low-grade inflammation as in aging and antiretroviral therapy (ART)-suppressed HIV infection is not known. In this study, we made use of stored samples from the FLORAH cohort of HIV-infected ART-suppressed adults (age range 19–77 years.) and age-matched HIV-uninfected controls. We measured the expression levels of ICMs: PD-1, LAG-3, TIGIT, TIM-3, and 2B4 on resting CD4 and CD8 T cells and maturation subsets. To determine how expression of these molecules can affect T cell function, we stimulated peripheral blood mononuclear cell with HIV Gag or p09/H1N1 antigen and performed intracellular cytokine staining by multiparameter flow cytometry. ICMs were expressed at higher levels in CD8 compared with CD4. PD-1 was the only molecule that remained significantly higher in HIV-infected individuals compared with controls. LAG-3 expression increased with age in CD4 and CD8 T cells. 2B4 expression on CD8 T cells was negatively associated with IL-2 production but showed no effect on CD4 T cell function. TIM-3 expression was negatively associated with IL-21 production in CD4 and CD8 T cells and also negatively correlated with flu vaccine responses in HIV-negative individuals. Taken altogether, this study demonstrates the marked variation in ICM expression in T cells among adults and sheds light on the biology of these molecules and their effects on antigen-specific T cell functions. Overall, our results point to TIM-3 as a potential biomarker for immune function in HIV(+) individuals on ART.